Prevalence of Dysmenorrhea and its Correlates among the Rural Women of Andhra Pradesh, India (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: dysmenorrhea; menstrual cycle; socioeconomic status; life styles; rural women